Mono‐ and Di‐Fucosylated Glycans of the Parasitic Worm S. mansoni are Recognized Differently by the Innate Immune Receptor DC‐SIGN. Issue 67 (22nd October 2020) - Srivastava, Apoorva D.; Unione, Luca; Wolfert, Margreet A.; Valverde, Pablo; Ardá, Ana; Jiménez‐Barbero, Jesús; Boons, Geert‐Jan
Abstract: The parasitic worm, Schistosoma mansoni, expresses unusual fucosylated glycans in a stage‐dependent manner that can be recognized by the human innate immune receptor DC‐SIGN, thereby shaping host immune responses. We have developed a synthetic approach for mono‐ and bis‐fucosylated LacdiNAc (LDN‐F and LDN‐DF, respectively), which are epitopes expressed on glycolipids and glycoproteins of S. mansoni . It is based on the use of monosaccharide building blocks having carefully selected amino‐protecting groups, facilitating high yielding and stereoselective glycosylations. The molecular interaction between the synthetic glycans and DC‐SIGN was studied by NMR and molecular modeling, which demonstrated that the α1, 3‐fucoside of LDN‐F can coordinate with the Ca 2+ ‐ion of the canonical binding site of DC‐SIGN allowing for additional interactions with the underlying LDN backbone. The 1, 2‐fucoside of LDN‐DF can be complexed in a similar manner, however, in this binding mode GlcNAc and GalNAc of the LDN backbone are placed away from the protein surface resulting in a substantially lower binding affinity. Glycan microarray binding studies showed that the avidity and selectivity of binding is greatly enhanced when the glycans are presented multivalently, and in this format Le x and LDN‐F gave strong responsiveness, whereas no binding was detected for LDN‐DF. The data indicates that S. mansoni has developed a strategy to avoid detection by DC‐SIGN in a stage‐dependent manner by the addition of a fucoside to a number of its ligands. Abstract : Chemically synthesized oligosaccharides derived from the parasite worm S. mansoni made it possible to investigate by a combination of analytical techniques molecular interactions with the innate immune receptor DC‐SIGN. It showed that by further fucosylation of antigens such as LDN‐NF, detection by DC‐SIGN is prevented, which in turn may be important for shaping immune responses during different phases of the life cycle of the parasite.